PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION TERHADAP KETERAMPILAN MENULIS TEKS LAPORAN HASIL OBSERVASI - Lifia Yola Febrianti (Sekolah Pascasarjana Universitas Pendidikan Indonesia, 2016)
The purpose of this study is, to describe the impact of using learning model investigations on the skill of writing texts report the observation of the seventh grade students of SMPN 2 Lubuk Alung. The method used in this research was experimental. Based on the results of data analysis can be concluded, that the text of the report writing skills of observation, after the investigation of cooperative learning group, better than the previous condition. This shows that the model of cooperative learning type group investigation can be utilized as an alternative model of learning writing skills text of the report on the observation.Keywords: learning model, group investigations, text report writing skills.